Strengthen Your Team’s CLA Practices: Introducing the CLA Maturity Too l for USAID Implementers (Social Impact , Inc, 2023)
The Collaborating, Learning & Adapting (CLA) Maturity Tool has been us ed by USAID operating units since 2015. The tool enables staff to self -assess their current CLA practice and plan ways to improve their inte rnal and external collaboration, organizational learning efforts, and adaptive management practices. Recently, SI built on this resource to create the CLA Maturity Tool for implementing partners (IPs) to provid e a version that speaks more directly to the experience of internation al and local organizations. Learn more here.